KINESTHETIC INTELLIGENCE AND ITS RELATION TO MOTOR SATISFACTION IN THE FENCING SKILL OF THRUST AMONG FEMALE STUDENTS OF THE FACULTY OF PHYSICAL EDUCATION AND SPORTS SCIENCES – AL-MUTHANNA UNIVERSITY - Abdul Rasool, Mohammed Dia (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2025)
The importance of this research lies in linking mental work (kinesthetic intelligence) with motor satisfaction in some offensive skills in fencing. The research problem, observed by the researcher through close monitoring, identified many instances of unsuccessful attacks, leading to the loss of winning opportunities in critical situations. This may be attributed to deficiencies in kinesthetic intelligence or the self-perception and satisfaction of individuals. Understanding this psychological phenomenon aids in developing an essential factor in successful attacks. The study aimed to identify the level of kinesthetic intelligence among female students of the Faculty of Physical Education and Sports Sciences at Al-Muthanna University, assess motor satisfaction with offensive skills, and explore the relationship between kinesthetic intelligence and motor satisfaction. The hypothesis posited a significant relationship between kinesthetic intelligence and motor satisfaction in fencing offensive skills. Chapter two reviewed theoretical studies, addressing intelligence, kinesthetic intelligence, motor satisfaction, and offensive skills in fencing. Chapter three outlined the research methodology and fieldwork. The descriptive method, utilizing survey and correlational techniques, was applied to a sample of 15 female students out of 20, randomly selected. The researcher also conducted a pilot study, primary experiments, and employed statistical methods. Chapter four presented, analyzed, and discussed the results. Chapter five concluded the findings, highlighting that kinesthetic intelligence significantly correlates with motor satisfaction in fencing offensive skills and providing recommendations for enhancing psychological aspects in training programs to improve motor performance.